1997
DOI: 10.1002/(sici)1098-2418(199709)11:2<179::aid-rsa5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Properly colored Hamilton cycles in edge-colored complete graphs

Abstract: ABSTRACT:It is shown that, for ⑀ ) 0 and n ) n ⑀ , any complete graph K on n vertices 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 9 publications
(13 reference statements)
2
98
0
Order By: Relevance
“…which are properly colored and satisfy (1). Since b(C 1 , P 1 ) < b(C, P ) holds, our minimality assumption yields a PCHP as in Claim A, which is a contradiction.…”
Section: First We Suppose C(vmentioning
confidence: 99%
See 1 more Smart Citation
“…which are properly colored and satisfy (1). Since b(C 1 , P 1 ) < b(C, P ) holds, our minimality assumption yields a PCHP as in Claim A, which is a contradiction.…”
Section: First We Suppose C(vmentioning
confidence: 99%
“…The best result so far for 'small' values of n is by J. Shearer [12]: 7∆ mon < n/2 guarantees the existence of a properly colored Hamilton cycle. The best result so far for large values of n is due to N. Alon and G. Gutin [1]: For every > 0 and n = n large enough, ∆ mon ≤ (1 − 1 √ 2 − ) n/2 implies the existence of a properly colored Hamilton cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Bollobás and Erdös in [8], conjectured that if the monochromatic degree of every vertex in K c n is strictly less than n 2 , then K c n contains a properly edge-colored Hamiltonian cycle, for any c ≥ 3. This conjecture was partially proved in [1] by using an advanced probabilistic method. The conjecture below is a weaker version of that conjecture by Bollobás and Erdös for regular edge-colored complete graphs, and perhaps an easier one to prove.…”
Section: Proof Of the Assertionmentioning
confidence: 99%
“…Improving some previous results on this conjecture, Shearer [18] showed that if 7∆ mon (K c n ) < n, then K c n has a PC Hamilton cycle. So far, the best asymptotic estimate was obtained by Alon and Gutin [3]. …”
Section: Longest Pc Cycles and Paths In Edge-coloured Complete Graphsmentioning
confidence: 99%